Adolescent Health Series: Engagement with young people as partners in health research: Four case studies from Sub‐Saharan Africa. Issue 1 (17th December 2021) - Doyle, Aoife M.; Dziva Chikwari, Chido; Majozi, Nomathamsanqa; Simwinga, Musonda; Mayingire, Gracious R.; Simbeye, Kelvin; Dringus, Stefanie; Bernays, Sarah
Abstract: Objectives: Existing health services for young people (YP)(10–24 years), which are predominantly designed for but not with young people, often do not meet YP's needs. The 2018 Global Consensus Statement on meaningful adolescent and youth engagement affirms that YP have a fundamental right to actively and meaningfully engage in all matters that affect their lives. We present four case studies from three countries in sub‐Saharan Africa as practical examples of the engagement of young people as partners in health research. We critically reflect on best practices to inform and guide the increasing adoption of collaborative approaches. Methods: We developed a narrative summary of each case study through review of study documentation and discussions with research staff and young people. A youth engagement framework was used to describe partnership activities according to the following dimensions: purpose, process, positioning, perspective, power relations, place and protection. We reflected on innovative practices used, overall level of participation achieved and strategies to address ethical, logistical and/or financial barriers. Results: In all case studies, we found evidence of engagement activities that aligned with the Global Consensus Statement on Meaningful Youth Engagement. However, access to participation was often uneven and despite efforts, marginalised young people continue to have insufficient opportunities to engage. Furthermore, although young people had some opportunity to influence the research methods, many of the key design decisions had been determined prior to their involvement. In our case studies, researchers had built in insufficient opportunities to evaluate the level and impact of youth engagement. Conclusions: We therefore recommend early involvement of young people in the research process so that they can contribute to setting the research agenda, the design of planned studies and thus increase the scope of their engagement from the beginning. Youth engagement activities need to be evaluated from the perspective of all stakeholders including young people themselves with a focus on opportunities to engage, the level of engagement achieved and impact of engagement. From the beginning, researchers should provide space for learning, and involve young people in encouraging critical reflection of what does not yet work, as well as what does, to enable improvements.